Z biblioteki proboszcza antokolskiego ks. Benedykta Szamotulskiego - Czyż, Anna S. (Archiwa, Biblioteki i Muzea Kościelne, 2011)
The article presents five books, which were in possession of the Rev. Benedykt Szamotulski (1620-1686), one of the most active Canons Regular of the Lateral in the seventeenth–century Republic of Poland, the parish priest of the St Peter and St Paul’s Church in the Antakalnis in Vilnius. These are the titles which were identified thanks to the ownership entries: Andreae Alciati Emblemata cum commentariis Claudii Minois I. C. Francisci Sanctii Brocensis et Notis Laurentii Pignorii Patavini… (published in Padua in 1621), Vox turturis seu de Florenti usque ad nostra tempora SS. Benedicti, Dominici, Francisci... (published in Cologne in 1638), Xenia et sermones problematicae cum paradoxis et baculo (published in Mainz in 1647), Practica prudentiae politicae et militaris in 246 axiomata congesta... (published in Vilnius in 1670) and Vitis mystica. Viti verae, quae Christus est... (published in Cologne in 1677). Although the mentioned books are typical examples of private libraries of Canons Regular of the Lateral, they were used by the Rev. Benedykt Szamotulski for designing the ideological program of the interior of the St Peter and St Paul’s Church in the Antakalnis in Vilnius. A particularly valuable book in the Rev Szamotulski’s library was Vox turturis seu de Florenti usque ad nostra tempora SS. Benedicti, Dominici, Francisci…, . It was previously in possession of Władysław IV. The evidence of this ownership is superexlibris with the coat of arms of the House of Vasa with the Order of the Golden Fleece. So far, this book has not been mentioned in the literature on the book collections of the House of Vasa.